Effect of ammonium bisulfate on synergistic mercury removal over V2O5-based SCR catalysts - Jiajian Chen; Tingfeng Shan; Zhen Zhang; Jiali Peng; Hongmin Yang (Fuel, 2026)

Identification of a novel major QTL and F-box candidate genes controlling seed dormancy in common wheat - Yuxia Lyu; Yaoyao Zhao; Wenbo Lu; Xu Pan; Wei Gao; Litian Zhang; Huanfeng Wang; Zhaoyu Yu; Ruihan Wang; Tingfeng Shou; Bingbing Tian; Jiajia Cao; et al. (Theoretical and Applied Genetics, 2026)

Emergence of anthropogenic warming in Antarctica - Zihuan Zhang; Sai Wang; Deliang Chen; Tingfeng Dou; Cunde Xiao; Annette Rinke; Shoudong Zhao; Petra Heil; Wen Chen; Minghu Ding (Science Bulletin, 2026)

Unveiling the synergistic mechanism of lipid oxidation and protein glycosylation in the formation of advanced glycation end products in tilapia during thermal processing - Lijia Yang; Hanyao Liu; Penglong Liu; Tingfeng Zhang; Weifeng Liu; Yehui Zhang; Wangdong Li; Yang Liu; Tiantian Zhao (Food Research International, 2026)

Uranium release from iron-rich acid soils under IPCC elevated CO2 scenarios: One-sided organic nanocolloidal dominance rather than expected iron oxide colloids - Ziyan Wang; Tingfeng Cheng; Caiqin Wang; Yuwei Zhao; Daoyong Zhang; Xiangliang Pan (Journal of Hazardous Materials, 2025)

Resource utilization of spent lithium iron phosphate cathode materials for mineralizing phenol-containing wastewater by Fenton process - Bingyan Zhu; Rensheng Song; Liwei Pan; Yuanlong Liu; Zhibo Liu; Tingfeng Xue; Xinguang Li; Jing Zhang (Journal of Environmental Chemical Engineering, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Restoration of compacted soils using artificial pores under freeze–thaw conditions - Tingfeng He; Huiqing Zhang; Huatao Liu; Liu Enke; Qishuo Ding (Soil and Tillage Research, 2025)

Synergistic degradation of phenol in water by ozone and peroxymonosulfate with interfacial CoAl2O4@γ-Al2O3 catalyst - Tingfeng Xue; Jingcheng Wei; Bingyan Zhu; Zhibo Liu; Zongwei Zhang; Shuang Xu; Shuang Lv; Jing Zhang; Liwei Pan (Journal of Water Process Engineering, 2025)

A novel scene coupling semantic mask network for remote sensing image segmentation - Xiaowen Ma; Rongrong Lian; Zhenkai Wu; Renxiang Guan; Tingfeng Hong; Mengjiao Zhao; Mengting Ma; Jiangtao Nie; Zhenhong Du; Siyang Song; Wei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Inhibition of STRA6 suppresses NSCLC growth via blocking STAT3/SREBP-1c axis-mediated lipogenesis - Yue Zhou; Rong Zhou; Ning Wang; Tingfeng Zhao; Pan Qiu; Chenzi Gao; Meijia Chang; Ning Lin; Xu Zhang; John Zhong Li; Qian Wang (Molecular and Cellular Biochemistry, 2025)

Effect of flammable gases produced from coal smoldering on methane explosion limits under nitrogen dilution in coal mines - Dong Ma; Zhenfang Shi; Tingfeng Zhu; Leilin Zhang; Chungen Yin (Fuel, 2025)

Fast and Deterministic Underwater Point Cloud Registration for Multibeam Echo Sounder Data - Liang Zhao; Lan Cheng; Tingfeng Tan; Chun Cao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Investigating underwater environments using Multi-Beam Echo Sounder (MBES) point cloud registration technology is a critical yet underdeveloped area in oceanographic research. This paper presents a fast, deterministic Branch-and-Bound (BnB) method with four degrees of freedom, which combines Inertial Measurement Unit (IMU) data with MBES point cloud data for precise registration. Given the prevalence of outliers and noise in underwater acoustic measurements, the BnB method is employed to provide globally deterministic solutions. However, due to the exponential convergence speed of the BnB method with respect to the dimensionality of the solution space, searching within a six-degree-of-freedom parameter space (three rotational and three translational degrees of freedom) can be extremely time-consuming. To this end, the Z-axis of the point cloud is aligned with the gravitational direction of the IMU, reducing the rotational degrees of freedom from three to one, specifically concerning yaw. Additionally, an outlier exclusion strategy is introduced to eliminate mismatches, significantly reducing the number of key-point correspondences and thereby improving registration efficiency. Experiments conducted on both public and real-world lake datasets demonstrate that the proposed method achieves a favorable balance between speed and accuracy, outperforming other tested methods and meeting the demands of contemporary research.

Prototypical basin reconstruction and evolutionary models for the Precambrian of the Qinshui Basin, North China craton - Tianshun Liu; Wenlong Ding; Zhong Liu; Zhijun Li; Pengbao Zhang; Chuanli Peng; Xiaoyun Cheng; Tingfeng Liu; Tong Gou (Marine and Petroleum Geology, 2024)

Tungsten migration and transformation characteristics in lake sediments under changing habitats from algae to macrophytes - Xiang Chen; Yan Wang; Lan Zhang; Dongdong Zhu; Wenming Yan; Minjuan Li; Junliang Jin; Tingfeng Wu; Qi Li; Xiangyu He; Gongyao Wu; Yan Tian; et al. (Journal of Hazardous Materials, 2024)

In-situ inhibition mechanism of SO3 formation over MoS2 modified V2O5/TiO2 catalyst within selective catalytic reduction process - Tingfeng Shan; Zhen Zhang; Bowen Li; Qi Zhang; Xiangfu Wang; Yusi He; Hongmin Yang (Fuel, 2024)

Underwater Gyros Denoising Net (UGDN): A Learning-Based Gyros Denoising Method for Underwater Navigation - Chun Cao; Can Wang; Shaoping Zhao; Tingfeng Tan; Liang Zhao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Autonomous Underwater Vehicles (AUVs) are widely used for hydrological monitoring, underwater exploration, and geological surveys. However, AUVs face limitations in underwater navigation due to the high costs associated with Strapdown Inertial Navigation System (SINS) and Doppler Velocity Log (DVL), hindering the development of low-cost vehicles. Micro Electro Mechanical System Inertial Measurement Units (MEMS IMUs) are widely used in industry due to their low cost and can output acceleration and angular velocity, making them suitable as an Attitude Heading Reference System (AHRS) for low-cost vehicles. However, poorly calibrated MEMS IMUs provide an inaccurate angular velocity, leading to rapid drift in orientation. In underwater environments where AUVs cannot use GPS for position correction, this drift can have severe consequences. To address this issue, this paper proposes Underwater Gyros Denoising Net (UGDN), a method based on dilated convolutions and LSTM that learns and extracts the spatiotemporal features of IMU sequences to dynamically compensate for the gyroscope’s angular velocity measurements, reducing attitude and heading errors. In the experimental section of this paper, we deployed this method on a dataset collected from field trials and achieved significant results. The experimental results show that the accuracy of MEMS IMU data denoised by UGDN approaches that of fiber-optic SINS, and when integrated with DVL, it can serve as a low-cost underwater navigation solution.

Side-Scan Sonar Image Generator Based on Diffusion Models for Autonomous Underwater Vehicles - Feihu Zhang; Xujia Hou; Zewen Wang; Chensheng Cheng; Tingfeng Tan (Journal of Marine Science and Engineering, 2024)
In the field of underwater perception and detection, side-scan sonar (SSS) plays an indispensable role. However, the imaging mechanism of SSS results in slow information acquisition and high complexity, significantly hindering the advancement of downstream data-driven applications. To address this challenge, we designed an SSS image generator based on diffusion models. We developed a data collection system based on Autonomous Underwater Vehicles (AUVs) to achieve stable and rich data collection. For the process of converting acoustic signals into image signals, we established an image compensation method based on nonlinear gain enhancement to ensure the reliability of remote signals. On this basis, we developed the first controllable category SSS image generation algorithm, which can generate specified data for five categories, demonstrating outstanding performance in terms of the Fréchet Inception Distance (FID) and the Inception Score (IS). We further evaluated our image generator in the task of SSS object detection, and our cross-validation experiments showed that the generated images contributed to an average accuracy improvement of approximately 10% in object detection. The experimental results validate the effectiveness of the proposed SSS image generator in generating highly similar sonar images and enhancing detection accuracy, effectively addressing the issue of data scarcity.

Underwater Mapping and Optimization Based on Multibeam Echo Sounders - Feihu Zhang; Tingfeng Tan; Xujia Hou; Liang Zhao; Chun Cao; Zewen Wang (Journal of Marine Science and Engineering, 2024)
Multibeam echo sounders (MBESs) enable extensive underwater environment exploration. However, due to weak correlation between adjacent multibeam sonar data and difficulties in inter-frame feature matching, the resulting underwater mapping accuracy frequently falls short of the desired level. To address this issue, this study presents the development of a multibeam data processing system, which includes functionalities for sonar parameter configuration, data storage, and point cloud conversion. Subsequently, an Iterative Extended Kalman Filter (iEKF) algorithm is employed for odometry estimation, facilitating the initial construction of the point cloud map. To further enhance mapping accuracy, we utilize the Generalized Iterative Closest Point (GICP) algorithm for point cloud registration, effectively merging point cloud data collected at different times from the same location. Finally, real-world lake experiments demonstrate that our method achieves an Absolute Trajectory Error (ATE) of 15.10 m and an average local point cloud registration error of 0.97 m. Furthermore, we conduct measurements on various types of artificial targets. The experimental results indicate that the average location error of the targets calculated by our method is 4.62 m, which meets the accuracy requirements for underwater target exploration.

On the Shallowing of Antarctic Low-Level Temperature Inversions Projected by CESM-LE under RCP8.5 - Minghu Ding; Lin Zhang; Tingfeng Dou; Yi Huang; Yingyan Luo; Junmei Lyu; Cunde Xiao (Journal of Meteorological Research, 2024)

Balancing urban energy considering economic growth and environmental sustainability through integration of renewable energy - Mei Zhang; Danting Zhang; Tingfeng Xie (Sustainable Cities and Society, 2024)

A Statistical Linkage between Extreme Cold Wave Events in Southern China and Sea Ice Extent in the Barents-Kara Seas from 1289 to 2017 - Cunde Xiao; Qi Zhang; Jiao Yang; Zhiheng Du; Minghu Ding; Tingfeng Dou; Binhe Luo (Advances in Atmospheric Sciences, 2023)

Alkalization-induced disintegration increased redox activity of solid humic acids and its soil biogeochemical implications - Caiqin Wang; Shuting Tang; Hangzhe Chen; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

3D-imaging and quantitative assessment for size-related penetration of HfO2 nanoparticles in breast cancer tumor by synchrotron radiation microcomputed tomography - Jiali Wang; Tingfeng Zhang; You Liao; Wei Chen; Shanshan Liang; Si Xu; Hao Fang; Meng Wang; Lingna Zheng; Zhanjun Gu; Zhiyong Zhang; Bing Wang; et al. (Analytica Chimica Acta, 2023)

Electrochemical properties of humic acid and its novel applications: A tip of the iceberg - Caiqin Wang; Tingfeng Cheng; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Protective-mechanism-exclusive thermal stability modes of soil organic matter: Novel implication for wildfire effect on soil organic carbon - Caiqin Wang; Tingfeng Cheng; Shuting Tang; Mengxuan Li; Daoyong Zhang; Xiangliang Pan (Science of The Total Environment, 2023)

Affinity-based alleviation of dissolved organic matter (DOM) on tetracycline toxicity to photosynthesis of green algae Chlorella vulgaris: roles of hydrophilic and hydrophobic DOM - Caiqin Wang; Hang Xu; Tingfeng Cheng; Shuting Tang; Daoyong Zhang; Meichao Li; Xiangliang Pan (Environmental Science and Pollution Research, 2023)

On the drivers of temperature extremes on the Antarctic Peninsula during austral summer - Sai Wang; Minghu Ding; Ge Liu; Ting Wei; Wenqian Zhang; Wen Chen; Tingfeng Dou; Cunde Xiao (Climate Dynamics, 2022)

Decomposition and Nutrient Release into Water from Litter Mixtures of Coastal Wetland Species - Patrick Ndayambaje; Tingfeng Zhang; Lili Wei; Lin Liu; Xu Huang; Jie Li; Shaohua Tian; Yu Xin; Xuecong Sun; Chaoxiang Liu (Wetlands, 2022)

Extreme sea levels along coastal China: uncertainties and implications - Jiayi Fang; Thomas Wahl; Qiang Zhang; Sanne Muis; Pan Hu; Jian Fang; Shiqiang Du; Tingfeng Dou; Peijun Shi (Stochastic Environmental Research and Risk Assessment, 2021)
Extreme sea levels (ESLs) due to typhoon-induced storm surge threaten the societal security of densely populated coastal China. Uncertainty in extreme value analysis (EVA) for ESL estimation has large implications for coastal communities’ adaptation to natural hazards. Here we evaluate uncertainties in ESL estimation and relevant driving factors based on hourly observations from 13 tide gauge stations and a complementary dataset derived from a hydrodynamic model. Results indicate significant uncertainties in ESL estimations stemming from using different EVA methods, which then propagate to the inundation assessment. Amplification factors due to sea-level rise (SLR) are highly sensitive to local relative SLR and the shape of the exceedance probability curve, which in turn depends on the selected EVA method. The hydrodynamic model hindcast indicates that high ESLs mainly occurred in eastern coastal China due to typhoon-induced storm surge. Larger uncertainties in the modelled ESLs are found for the coasts of the Yangtze River Delta, and particularly in the river mouth region. Future research and adaptation planning should prioritize these regions given expected future rising sea level, compound flood events, and human-induced factors (e.g. subsidence). This study provides theoretical and practical references for adaptation to ESL-related hazards along coastal China, with implications for coastal regions worldwide.

Mechanism of phosphorus mobility in sediments with larval (Propsilocerus akamusi) bioturbation - Wenming Yan; Musong Chen; Ling Liu; Tingfeng Wu; Yi Zhang; Han Wang; Xigang Xing; Kongming Fan (Environmental Science and Pollution Research, 2020)

Reconstruction of autumn sea ice extent changes since AD1289 in the Barents-Kara Sea, Arctic - Qi Zhang; Cunde Xiao; Minghu Ding; Tingfeng Dou (Science China Earth Sciences, 2018)

Diversity and novelty of actinobacteria in Arctic marine sediments - Gaiyun Zhang; Tingfeng Cao; Jianxi Ying; Yanliu Yang; Lingqi Ma (Antonie van Leeuwenhoek, 2014)

Production of transgenic mice expressing the goat H-FABP gene by intratesticular injection - Hao Chen; Yanhui Yin; Yani Zhang; Min Sun; Tingfeng Chen; Caiye Zhu; Wei Li; Bichun Li; Huilin Yang (Molecular Biology Reports, 2013)

QTL underlying field grain drying rate after physiological maturity in maize (Zea Mays L.) - Zhenhua Wang; Xia Wang; Lin Zhang; Xianjun Liu; Hong Di; Tingfeng Li; Xiaochun Jin (Euphytica, 2012)